You have to stop this - Bosch, Pseudonymous. (Secret series ;, 2011)
When a mummy disappears from the local history museum while Cass and her friends Max-Ernest and Yo-Yoji are there, they try to solve the case in order to clear their names and, they hope, discover the Secret they have been seeking.